Decarbonization of the Romanian Economy: An ARDL and KRLS Approach of Ecological Footprint - Dan Ioan Topor; Andreea Marin-Pantelescu; Adela Socol; Oana Raluca Ivan (Amfiteatru Economic)
The mechanisms developed at the European level through the Green Deal, to achieve the assumed decarbonization process, are facing major challenges to reach climate neutrality of the EU in a clean and circular economy by 2050. The purpose of this study is to investigate the hypothesis of the Environmental Kuznets Curve (EKC), based on the causal relationship between the ecological footprint as an indicator of sustainable development, and several variables, namely the gross domestic product per capita (GDP per capita) to capture the growth of the economy, globalisation (KOF Globalisation Index), and two environmental variables: fossil fuel energy and CO2 emissions. The study was developed for Romania, for the period 1990 to 2018, and used Autoregressive Distributed Lag (ARDL), dynamic ARDL, and Kernel Regularised Least Squares (KRLS) models. The results indicate the existence of a relationship between variables, both in the long and short term and, also coexistence between the U-shaped and inverted U-shaped EKC graphs, which confirm the empirical results found in the literature. The originality of the research consists in analysing the decarbonization of the Romanian economy by studying the influence of economic growth, globalisation, and energy from fossil fuels and CO2 emissions on the ecological footprint. From the perspective of public policies, the results highlight the need to configure appropriate instruments aimed at climate neutrality according to the objectives assumed by Romania through the Green Deal of the European Union